Performance analysis in padel: a systematic review - Martín-Miguel, I.; Escudero-Tena, A.; Muñoz, D.; Sánchez-Alcaraz, B. J. (Journal of Human Kinetics, 2023)
The aim of the study was to carry out a systematic review of the most recent research on performance analysis in padel. An electronic search was made in four sport science databases: Web of Science, Pubmed, Scopus and Google Scholar. Systematic review principles were used to identify and select studies following inclusion and exclusion criteria. From a total of 261 articles identified in the initial search, 27 articles were included in analysis, all dating from after 2018. The articles were classified according to four study variables: temporal aspects, game actions, on-court movements and match score studies, ordered in turn according to the year of publication. The results show differences in the four study variables according to the gender or the level of players, the side or the zone of play and the duration of the match. In conclusion, the results define the relevant aspects of the game with the aim of being used at a technical, tactical and physical level, as well as contributing to the development of scientific knowledge in padel, allowing future research to address less studied topics and carry out more complete and specific studies and interventions for a greater understanding of the needs of padel.